LncRNA-mRNA co-expression network in the mechanism of butylphthalide treatment for ischemic stroke - An, Yangfang; Huang, Lingyun; Li, Jun; Chen, Zhuo; Cai, Jizhang; Wang, Biao; Zhou, Qiong (BMC neurology, 2025)
Butylphthalide has shown significant potential in the treatment of ischemic stroke, but its precise mechanisms of action remain unclear. Long non-coding RNAs (lncRNAs) and messenger RNAs (mRNAs) play crucial roles in the pathogenesis of ischemic stroke and may serve as potential therapeutic targets. This study investigated the effects of butylphthalide treatment on the lncRNA-mRNA co-expression network in ischemic stroke patients. Peripheral blood samples were collected from ischemic stroke patients treated with butylphthalide and from control subjects. mRNA and lncRNA expression profiles were obtained using microarray scanning, and differentially expressed lncRNAs (DElncRNAs) were validated by qRT-PCR. Target genes interacting with DElncRNAs were predicted using the miRTargetLink database. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed on both DElncRNAs and differentially expressed mRNAs (DEmRNAs). A protein-protein interaction (PPI) network was constructed for proteins encoded by DEmRNAs. Co-expression analysis, based on Pearson correlation coefficients, identified the top five mRNAs and lncRNAs with high connectivity. Finally, molecular docking was performed to investigate the binding interaction between butylphthalide and key mRNAs. A total of 86 differentially expressed mRNAs (69 upregulated, 17 downregulated) and 35 DElncRNAs (all upregulated) were identified. DEmRNAs were primarily associated with pathways related to cell receptors, signal transduction, cell proliferation, migration, and glucose metabolism, while DElncRNAs were involved in processes such as embryonic development, neuronal connectivity, and energy metabolism. Co-expression analysis identified key mRNA nodes (SETD9, ZNF718, AOC2, MPND, ODF1) and lncRNA nodes (IDH2-DT, CLEC12A-AS1, CARD8-AS1, LINC01275, ZNF436-AS1). Molecular docking analysis suggested that MT-CO1, SETD9, and ZNF718 could be potential targets of butylphthalide. Butylphthalide may exert its therapeutic effects by regulating the LncRNA-mRNA co-expression network, influencing energy metabolism and neuronal development. This provides new insights into its mechanism of action and potential therapeutic targets.